2004
DOI: 10.1093/aje/kwh072
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Constipation: Agreement among Several Criteria and Evaluation of the Diagnostic Accuracy of Qualifying Symptoms and Self-reported Definition in a Population-based Survey in Spain

Abstract: The aims of this study were to estimate the prevalence of chronic constipation and to evaluate the diagnostic accuracy of the symptoms and the self-reported definition of constipation. A cross-sectional survey was conducted in the general community in 1999. A questionnaire comprising 21 items was developed and mailed to a random sample of 489 subjects who were aged between 18 and 65 years and who belonged to a Spanish population. In the 349 subjects (71%) responding to the questionnaire, the prevalence of self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
134
3
37

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(186 citation statements)
references
References 23 publications
12
134
3
37
Order By: Relevance
“…The proportion of the subjects who were considered 'constipated' in the present study seemed to be relatively high (26%); some of those may not be classified as 'constipated' according to symptombased criteria such as Rome I and Rome II criteria (Thompson et al, 1999). In fact, the prevalence of self-reported constipation was much higher compared with the prevalence based on Rome I and Rome II criteria in a study of Spain (30 vs 19 and 14%) (Garrigues et al, 2004). Thus, whether the same associations we observed would hold for constipation according to symptom-based criteria is not known, which should be addressed in future studies.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…The proportion of the subjects who were considered 'constipated' in the present study seemed to be relatively high (26%); some of those may not be classified as 'constipated' according to symptombased criteria such as Rome I and Rome II criteria (Thompson et al, 1999). In fact, the prevalence of self-reported constipation was much higher compared with the prevalence based on Rome I and Rome II criteria in a study of Spain (30 vs 19 and 14%) (Garrigues et al, 2004). Thus, whether the same associations we observed would hold for constipation according to symptom-based criteria is not known, which should be addressed in future studies.…”
Section: Discussioncontrasting
confidence: 67%
“…The reported prevalence of constipation ranges from 2 to 30% in Western countries, depending on the definition applied (Garrigues et al, 2004;Higgins and Johanson, 2004). In Japan, the prevalence of constipation, defined as p3 bowel movements weekly, also seems to be relatively high (6-25%) (Hirai and Takezoe, 1997;Hirai et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…A constipation questionnaire was developed based on a previous study (Garrigues et al, 2004) and incorporated into the 20-page questionnaire for lifestyle during the previous 6 years. We used the definition of functional constipation recommended by an international workshop on the management of constipation (Rome I criteria) (Whitehead et al, 1991).…”
Section: Constipationmentioning
confidence: 99%
“…We used the definition of functional constipation recommended by an international workshop on the management of constipation (Rome I criteria) (Whitehead et al, 1991). Although the Rome I criteria were modified in 1999 to the Rome II criteria (Thompson et al, 1999), epidemiologic studies have consistently shown that the latter may be too restrictive for the diagnosis of constipation (Pare et al, 2001;Garrigues et al, 2004), and we therefore used the former. The following four questions were used to assess Rome I-defined functional constipation: (1) Do you strain during a bowel movement?…”
Section: Constipationmentioning
confidence: 99%
See 1 more Smart Citation